2022
DOI: 10.1093/rheumatology/keac541
|View full text |Cite|
|
Sign up to set email alerts
|

Vision transformer assisting rheumatologists in screening for capillaroscopy changes in systemic sclerosis: an artificial intelligence model

Abstract: Objectives The first objective of this study was to implement and assess the performance and reliability of a vision transformer (ViT)-based deep-learning model, an ‘off-the-shelf’ artificial intelligence solution, for identifying distinct signs of microangiopathy in nailfold capilloroscopy (NFC) images of patients with SSc. The second objective was to compare the ViT’s analysis performance with that of practising rheumatologists. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…AUTOCAPI measures capillary density for a single field of view (preselected by the operator) [ 16 ]. Capillary.io [ 13 ] and a system developed by Swiss researchers [ 14 ] both detect vessels and signs of abnormality (e.g. giant capillaries, microhaemorrhages) from a single field of view (as opposed to a nailfold mosaic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AUTOCAPI measures capillary density for a single field of view (preselected by the operator) [ 16 ]. Capillary.io [ 13 ] and a system developed by Swiss researchers [ 14 ] both detect vessels and signs of abnormality (e.g. giant capillaries, microhaemorrhages) from a single field of view (as opposed to a nailfold mosaic).…”
Section: Discussionmentioning
confidence: 99%
“…The number of capillaries divided by the distance in mm from the left-most to right-most capillary was computed to quantify vessel density. Other investigators have included micro-haemorrhages [ 13 , 14 ]; we did not because they are difficult to define and are not necessary for diagnosis of SSc [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…22 The proximal nailfold is a preferred location for evaluation of the capillary loops because in this location they run parallel to the skin surface, enabling better visualization. 23 Also the scalp may fulfill this criterion of easy visualization of capillaries. Kwiatkowska et al 24 reported that vessels found on trichoscopy of 17 patients with systemic sclerosis were more commonly arranged into random, linear and clustered pattern in comparison to healthy controls.…”
Section: Syste M Ic Scl E Rosismentioning
confidence: 99%
“…Nailfold capillaroscopy is a well established method of assessing microangiopathy in the course of systemic sclerosis 22 . The proximal nailfold is a preferred location for evaluation of the capillary loops because in this location they run parallel to the skin surface, enabling better visualization 23 . Also the scalp may fulfill this criterion of easy visualization of capillaries.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Furthermore, ML frameworks were developed to predict rapid coronary plaque progression to identify patients at risk, as well as to assess the importance of clinical parameters [17]. Similarly, Garaiman et al assessed the performance of vision transformer (deep learning image based model) for identifying distinct signs of microangiopathy using nailfold capilloroscopy images of patients with SSc [18].…”
Section: Introductionmentioning
confidence: 99%